Vivere in tempi di crisi: I giovani portoghesi e la transizione dal mondo scolastico a quello lavorativo nel corso dell’ultimo decennio - Simões, F. (La condizione giovanile in Italia: Rapporto Giovani 2023, 2023)
For the past 10 years, young Portuguese people's prospects of achieving a full, independent life have been challenged: firstly, by the effects of the 2008 economic crisis and then by the consequences of the COVID-19 pandemic. In the meantime, major European Union instruments, such as the Youth Guarantee or, more recently, the Next Generation EU have set policy measures with implications for the younger generations’ transition from school to work. This report focuses on how young Portuguese people have coped with the job market inclusion demands between the economic and a health-related crisis.